A Quantitative Investigation into the Correlation between Snapchat use and the Self- Esteem of Generation Y, in Durban - Maharaj, Shivkriti (The IIE, 2020)
Over the last decade, recent developments in wireless technologies have presented novel means and directions of communication, which have transformed social media into a fundamental facet of modern society. Image-based platforms such as Snapchat have become increasingly popular amongst the younger generation and have introduced a new pattern of social comparison and interaction online. However, despite this proliferation of use, the literature remains divided regarding the latent impact of image-based social media platforms on users. Research regarding the Snapchat application and self-esteem in the South African context is also scant. The present study sought to establish if there is a correlation between Snapchat usage and the self-esteem of users within a South African context. This study was conducted using the application of the positivist quantitative approach. To meet the objectives of the study, 22 respondents between the ages of 24-39 years were selected as the target population and the non-probability method of snowball sampling was utilised. A questionnaire was used to obtain raw data pertaining to the specific phenomena of this study. The analysis indicated that there is a strong negate e relationship between Snapchat usage and the self-esteem levels of users. The results of the study elucidate that the intensity of usage may serve as a mediating variable in this relationship. The results also explicate that users who engage with Snapchat more frequently tend to exhibit lower levels of self-esteem as compared to those who use the application less frequently. The results from this study clearly illustrate the need for further research on the topic both globally and in South Africa. Future studies may benefit from utilizing an experimental research design to examine the cause and effect relationship between the two variables.
Keywords: Social media; Snapchat; Social comparison; Self-esteem; Intensity of usage